New insights on the use of the Fairtrade social premium - Jorge Sellare (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
Fairtrade standards differentiate themselves from other sustainability standards such as Rainforest Alliance and UTZ by demanding that buyers pay to farmers at least a minimum price and a Fairtrade social premium - a sum that is paid to cooperatives in addition to the agreed price to be used in projects to strengthen the cooperative and to benefit the community in the villages more broadly. The latter is often mentioned in the literature as one of the key mechanisms through which Fairtrade engenders changes in the small farm sector. However, no previous study has explicitly analyzed what the social premium is used for, which factors affect the decision-making processes, and whether farmers, workers, and the local communities more broadly benefit from projects implemented with the premium money. In this article, Iuse multivariate statistical techniques to analyze how patterns in the use of the premium are related to cooperatives'organizational characteristics. To illustrate the potential benefits of the social premium to the local community, Iuse regression analyses to evaluate the effects of certification and educational projects financed with the social premium on household education expenditure. Ifind evidence that living in a village where an educational project was implemented has a positive effect on education expenditure among farmers, but does not have an effect among rural workers.
Keywords: O12; Q01; Q12; Q13; 330; certification; cooperatives; Fairtrade premium; social premium; sustainability standards